Financial sector transparency, financial crises and market power: A cross-country evidence - Baah Aye Kusi; Elikplimi Komla Agbloyor; Agyapomaa Gyeke-Dako; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
The study investigates how financial sector transparency moderates the influence of financial crises on bank market power across seventy-five economies between 2004 and 2014. Employing two-step dynamic system generalized method of moments the study shows that while public sector-led financial sector transparency reduces bank market power, private sector-led financial sector transparency promotes bank market power given that private sector-led transparency gives financial cost advantage to financially sound banks to solidify the market power and dominance. Similarly, while financial crises reduce the market power of banks implying that during financial crises banks lose their market power, financial sector transparency promotes the negative effect of financial crises on bank market power. This implies that during financial crises, financial sector transparency whether enforced through private or public sector, boosts the weakening effect of financial crises on bank market power. These findings imply that regulators can rely on financial transparency to tame bank market power to enhance banking competitiveness. The findings and results are consistent even when country, time and continental effects are controlled for.
Keywords: 330; Market Power; Bank; Financial Sector Transparency; Private Sector; Public Sector